Neuropatia sensitiva periférica induzida por oxaliplatina em camundongos: influência do Diabetes Mellitus e o efeito protetor da metformina - Pereira, Lus Mário da Silva (2017)
Retrospective clinical studies have shown no significant statistical difference between diabetic and non-diabetic patients to present peripheral sensory neuropathy (PSN) using cumulative doses of oxaliplatin (OXL). These studies, however, present limitations on the reduced number of patients investigated and the difficulty to obtain a control group compatible with the treated group and exclusion of patients with initial degrees of neuropathy. Metformin (MTF) is an oral antihyperglycemic drug widely used in the treatment of type 2 diabetes mellitus. Studies have also shown important role of MTF in the fight against cancer and neuropathy caused by chemotherapy. In the present study, we aimed to study whether a pre-existing condition of diabetes mellitus (DM) could influence the onset and / or course of OXL-induced PSN and the protective effect of MTF on OXL-induced PSN. DM and PSN were each induced with alloxan (50 mg/kg, iv) single dose and OXL (4.0 mg/kg, iv) twice a week for 4.5 weeks respectively in mice that were evaluated weekly for 35 or 56 days. Nociceptive tests (Von Frey, rota-rod and tail immersion test) were performed on blood glucose and weight-for-weight measurements before and after animal treatments weekly or biweekly. After the 35- or 56-day periods the pancreas, dorsal root ganglion (DRG) and spinal cord (SC) of the animals were removed for immunofluorescence and analysis for neuronal activation protein (c-Fos) and transcription factor and activation 3 (ATF-3). The results showed that alloxan (50 mg/kg, iv) was the best dose capable of inducing DM in the animals without causing neuropathy or altering the reaction time in the animals in the rota-rod in relation to the control group. OXL (4.0 mg/kg, iv) was the best dose able to induce PSN in animals without altering the motor coordination of the animals in the spinning rod. The combination of the treatments with the best doses of alloxan and OXL induced DM with hyperglycemia and weight loss in animals significantly (p <0.05) compared to the control and OXL groups. OXL treatment induced PSN from the 28th day in the animals. In addition, the combination of alloxan and OXL treatments in addition to anticipating the PSN from the 28th day to the 21st day also amplified the establishment of the PSN in the animals compared to the OXL group. Analysis of the pancreas of the animals treated with alloxan and combined with OXL showed a decrease in the number of islets of Langerhans besides the presence of areas with intense basophilia and acinar cells with basophilic cytoplasm and disarrangement of the glandular architecture in comparison to the control group. Treatment of the animals with OXL combined with MTF (250 mg/kg, po) decreased the intensity of the PSN, and delayed tail removal time from animals from day 14 to day 28 significantly compared to OXL group. In addition, we observed increased immunoexpression of c-Fos and ATF-3 in the DRG of OXL-treated animals significantly compared to the control group. Already the treatment of the animals with MTF combined with OXL decreased the immunoexpression of c-Fos and ATF-3 in the animals DRG significantly compared to the OXL group. We also observed increased ATF-3 immunoexpression in SC of OXL-treated animals significantly compared to the control group, which was prevented by treatment of the MTF animals. There was no significant difference in c-Fos immunoexpression in SC between the treated groups and control. In the present study, the use of mice with DM associated with alloxan-induced hyperglycemia both anticipated and amplified the development of OXL-induced PSN. Additionally, we have demonstrated that the neuroprotective role of MTF probably occurs in the peripheral nervous system due to the decrease of c-Fos immunoexpression in the DRG, and there is no decrease in the immunoexpression in the SC.